The Effectiveness of Community Policing Programs in Enhancing Public Trust in the Indonesian National Police (Polri) in Urban Areas - Farid, Muhammad Imam (Indonesian National Police Academy, 2025)
The research evaluates how community policing initiatives affect public trust toward the Indonesian National Police (Polri) in fast-growing urban regions. The research evaluates program effectiveness by analyzing both empirical studies and official documents from 2001 to 2025 through Social Capital Theory. The research examined social capital through three dimensions which included Police-Community Partnership Forums (FKPM) for bonding and procedural justice and Patroli Perintis Presisi training for bridging and transparent communication through the “Presisi” app for linking. The research demonstrates that active FKPM initiatives lead to a 15% increase in crime reporting and procedural justice training improves officer–community relations and digital platforms maintain continuous two-way communication. The implementation of community policing faces ongoing challenges because of insufficient resources and institutional opposition. The research demonstrates that community policing stands essential for enhancing safety and legitimacy in urban Indonesia while recommending customized approaches and additional studies to understand local conditions and structural obstacles which provide knowledge for developing nation policing practices.